Effects of online learning on mental health in nursing students: A systematic review - Quyen, Nguyen Thi; Sofia, Lili; Tzu-Ting, Liao; Mulyoto, Raufina Riandhani (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Aim: This systematic review aims to explore the effect of online learning on mental health among nursing students. Method: The systematic review was conducted for relevant articles published in all languages from 2014 to 2024 in four electronic databases (PubMed, CINAHL, Cochrane Library, MEDLINE). The search terms included ‘nursing student’, ‘online learning’, and ‘stress’. Studies that were randomized controlled trials or quasi-experimental studies were included. Results: A total of 2367 articles were found in 4 databases, and 1 randomized control trial was included as the final result. The study results show that nursing students who received the virtual clinical simulation gained a higher anxiety level compared with those who joined the face - to - face program. Conclusion: Online learning causes more anxiety for nursing students than the face - to - face program. However, more RCT or quasi - experimental studies are needed to confirm this conclusion more convincingly.